2020
DOI: 10.1519/jsc.0000000000003831
|View full text |Cite
|
Sign up to set email alerts
|

Acute Resistance Exercise Reduces Postprandial Lipemia and Oxidative Stress in Resistance-Trained Men

Abstract: McAllister, MJ, Steadman, KS, Renteria, LI, Case, MJ, Butawan, MB, Bloomer, RJ, and McCurdy, KW. Acute resistance exercise reduces postprandial lipemia and oxidative stress in resistance-trained men. J Strength Cond Res 36(8): 2139–2146, 2022—Acute ingestion of a high-fat meal (HFM) results in significant increases in postprandial triacylglycerols (TAG) and markers of oxidative stress (OS). Combined aerobic and resistance exercise can attenuate postprandial lipemia; however, it is not clear if acute resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
0
8
1
1
Order By: Relevance
“…Since 2014, 36 studies have confirmed that exercise performed on the evening prior to a morning high-fat meal (that is, a meal containing above 0.7 g of fat per kg body mass) lowers PPL, compared to no exercise. This has been shown in young, middle-aged and/or older men [14,21,[33][34][35][36][37][38][39][40][41][42]22,43,76,77,23,[27][28][29][30][31][32], young men and women [44], young or middle-aged women [45,67], normal and overweight individuals [68], overweight and obese individuals [24,46,47] and adolescent boys and girls [48][49][50][51][52][53].…”
Section: Exercise Performed On the Day Preceding A High-fat Mealmentioning
confidence: 84%
See 3 more Smart Citations
“…Since 2014, 36 studies have confirmed that exercise performed on the evening prior to a morning high-fat meal (that is, a meal containing above 0.7 g of fat per kg body mass) lowers PPL, compared to no exercise. This has been shown in young, middle-aged and/or older men [14,21,[33][34][35][36][37][38][39][40][41][42]22,43,76,77,23,[27][28][29][30][31][32], young men and women [44], young or middle-aged women [45,67], normal and overweight individuals [68], overweight and obese individuals [24,46,47] and adolescent boys and girls [48][49][50][51][52][53].…”
Section: Exercise Performed On the Day Preceding A High-fat Mealmentioning
confidence: 84%
“…TAG reduction of 22% (range 4 to 35%) [14,28,[37][38][39][40][41][42][43][44][45][46]29,[47][48][49][50][51][52][53][54][55][56]30,[57][58][59][60][61][62][63][64][65][66]31,67,68,[32][33][34][35][36]. iv.…”
Section: Accepted Manuscriptunclassified
See 2 more Smart Citations
“…Exercise increases fat oxidation after meals ( 107 , 108 ). McAllister et al ( 109 ) explored the effect of acute moderate resistance exercise on alleviating postprandial oxidative stress and found that the AUC of advanced oxidation protein products at 4 h after meal was significantly lower than that at rest, and total nitrate/nitrite increased, illustrating that acute resistance exercise can reduce postprandial oxidative stress ( Table 1 ).…”
Section: Interventions On Postprandial Lipemiamentioning
confidence: 99%